Derivation For Rectangular Notch:: Area of Strip Da B X DH DQ VXBXDH DQ BXDHXV
Derivation For Rectangular Notch:: Area of Strip Da B X DH DQ VXBXDH DQ BXDHXV
Derivation For Rectangular Notch:: Area of Strip Da B X DH DQ VXBXDH DQ BXDHXV
Area of Strip = dA = B x dh
dQ = v x B x dh
d Qth = B x dh x vth
H
∫ d Qth = ∫ B dh V th
0
∫dQ th = ∫ B dh √ 2 gh
0
Qth = B √ 2 g ∫ √ h dh
0
3
2
Qth = B√ 2 g | h |
3/2
3
2
Qth = B√ 2 g ( H )
3/2
3
2 2
Qth = B√ 2 g H
3
2 3
Qth = B√ 2 g H 2
3
Qth = Krectangular H3/2
Derivation for Triangular Notch:
B /2
Tanθ =
H−h
B /2
Tanθ =
H−h
B
(H-h ) =
2
θ
d Qth = 2 (H-h) tan x Vth
2
Integrating both sides
H
θ
∫ dQ = ∫ 2 ( H−h )tan 2 V
th th
0
H
θ
2√ ∫
Qth = 2 tan 2 g (H−h) √ h dh
0
H
θ
2 g (H √h−h √ h) dh
2√ ∫
Qth = 2 tan
0
H
θ
Qth = 2 tan √ 2 g ∫ ¿ ¿ )dh
2 0
3 5
2 2
θ H h
Qth = 2 tan √ 2 g H 3/2 − 5
2
2
θ 2 2
Qth = 2 tan 2 g .H H3/2 – H5/2
2√ 3 5
8 θ
Qth = tan √ 2 g H5/2
15 2
Qth = KTriangular H5/2